The Detective as Historian : History and Art in Historical Crime Fiction - Kreiser, Lawrence A., 1969-; Browne, Ray B. (Ray Broadus), 1922-2009 (Book collections on Project MUSE., 2000)
"The crime fiction examined here covers virtually all of recorded history - from ancient Egypt through classical Greece and Rome; from medieval Europe through nineteenth-century England and America. The essays in this collection analyze and evaluate these works and demonstrate that they are not only gripping stories in their own right, but also the nerve center for historians of all stripes - from the professional to the most casual minded - to learn about past societies. People of the past appear with all their pretenses down and their acts of violence laid bare."--Jacket